DETERMINANTS OF DISCLOSURE OF SUSTAINABILITY REPORTS IN LQ 45 COMPANIES LISTED ON IDX 2014 - 2018 - Meiliyah Ariani; Zulhawati; Hermiyetti (Moestopo International Review on Social, Humanities, and Sciences, 2021)
This study aims to determine and analyze net profit margin, debt ratio, and dividend policy on Sustainability Reporting disclosure. The research sample used was 13 companies with the period 2014-2018. The sampling technique used purposive sampling technique. The data used in this study is using secondary data. The method used is a multiple regression technique that tests the variables of the panel data using SPSS 25. The results of this study indicate that net profit margin has a significant positive effect on Sustainability Reporting disclosure. With the increase in NPM (net profit margin), it will increase investor confidence in the company, so that the company's demands for its efforts in environmental and social performance are also higher. Debt ratio has a significant positive effect on Sustainability Reporting disclosure. The increase in the debt ratio shows the company's high need for fresh funds, the high value of the debt ratio also reveals the company's dependence on debt which can create risks for the company's survival. Dividend policy has a significant positive effect on Sustainability Reporting disclosure. The higher the level of dividend payments of a company, the level of disclosure in the Sustainability Report is also high.